Analisis Perilaku Biaya: Suatu Studi Komparasi Konsep Teoritis dan Praktik Pada Biaya Operasional (Perusahaan Jasa) - Nimas Ayu Astuti; Anggun Ayunda Lestari; Egintha Pratiwi Br Saragih; Alfia Adhatul Annisa; Fara Nia Williana (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study aims to analyze the operational cost behavior within the context of service companies, comparing theoretical concepts with practical applications. Methodologically, a comprehensive review of literature and theoretical frameworks on cost behavior was conducted to establish foundational concepts. The study also analyzed case studies and empirical data from various service sectors to illustrate practical applications and variations in cost behavior. The research focused on identifying direct costs such as direct labor and direct materials, as well as indirect costs including administrative overhead and marketing expenses. The results indicate that while direct costs in service companies may differ from those in manufacturing, they still play a crucial role in cost structures. Direct labor costs, for instance, often exhibit characteristics of both fixed and variable costs depending on payment methods and service delivery models. Indirect costs generally tend to behave more like fixed costs due to their stability over short-term changes in service volumes. The discussion underscores the complexities of managing indirect costs, suggesting that despite being categorized as fixed, they may vary in response to operational changes or broader strategic shifts. This variability emphasizes the importance of flexible budgeting and tailored cost control measures within the specific context of service companies. In conclusion, effective cost management in service companies requires a profound understanding of cost behavior and its implications for financial planning and decision-making. Recommendations include adopting technology-driven cost monitoring systems, enhancing transparency in cost allocation, and continuously evaluating cost structures to align with strategic objectives.